2014
DOI: 10.1186/1472-6831-14-121
|View full text |Cite
|
Sign up to set email alerts
|

Forgoing dental care for economic reasons in Switzerland: a six-year cross-sectional population-based study

Abstract: BackgroundWhile oral health is part of general health and well-being, oral health disparities nevertheless persist. Potential mechanisms include socioeconomic factors that may influence access to dental care in the absence of universal dental care insurance coverage. We investigated the evolution, prevalence and determinants (including socioeconomic) of forgoing of dental care for economic reasons in a Swiss region, over the course of six years.MethodsRepeated population-based surveys (2007–2012) of a represen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
26
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 40 publications
(73 reference statements)
6
26
0
2
Order By: Relevance
“…A recent study carried out in Switzerland yielded findings similar to our own, and pointed out the importance of opportunity costs as risk factors for forgoing healthcare, which would increase during an economic downturn 30. A cohort study took place in Iceland, limited to the years 2007–2009.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…A recent study carried out in Switzerland yielded findings similar to our own, and pointed out the importance of opportunity costs as risk factors for forgoing healthcare, which would increase during an economic downturn 30. A cohort study took place in Iceland, limited to the years 2007–2009.…”
Section: Discussionsupporting
confidence: 62%
“…It also appears that the crisis itself has had a larger impact on women compared with men (OR of 1.21 compared with 1.06). Guessous et al 30 found that women are more likely to forgo dental care for economic reasons when compared with men. Women would therefore be more exposed to the costs of healthcare than men, since they have historically assumed a caregiving role for the rest of their family.…”
Section: Discussionmentioning
confidence: 99%
“…The Icelandic economic collapse in 2008 seems to have had minor effects on dental care utilization . Studies from Spain 2007‐2011 and Switzerland 2007‐2012 have on the other hand found increased unmet need for dental care in low‐income groups, and similar reports come from Cypriot dentists . Also statistics from Eurostat, using the same data source as the present study, indicate that abstentions from dental care for financial reasons have become more widespread since 2008.…”
Section: Introductionmentioning
confidence: 94%
“…Oral health problems are more prevalent in lower social strata, but those with higher incomes and better education use more dental health services . Socioeconomic inequalities in dental care could even have widened in Europe during the global economic crisis which started in 2007.…”
Section: Introductionmentioning
confidence: 99%
“…Lietuvos Respublikos Konstitucinis Teismas pažymėjo, kad: ,,<...> reguliuojant privalomojo sveikatos draudimo santykius įstatymų leidėją saisto iš Konstitucijos 53 straipsnio 1 dalies kylantis reikalavimas užtikrinti visiems vienodą kokybiškų sveikatos priežiūros paslaugų prieinamumą; valstybės pareiga sukurti visuomenės solidarumu pagrįstą sveikatos priežiūros finansavimo viešosiomis lėšomis sistemą, kuri leistų užti-krinti pakankamą sveikatos priežiūros prieinamumą, negali būti aiškinama taip, esą visuomenė turi prisiimti visų įmanomų asmens sveikatos priežiūros paslaugų finansavimo naštą; šioje srityje būtina rasti sprendimus, užtikrinančius pusiausvyrą tarp asmens, kaip sveikatos priežiūros paslaugų vartotojo (paciento), ir visos visuomenės interesų; asmens sveikatos priežiūros finansavimo teisiniu reguliavimu turėtų būti sudarytos paskatos kiekvienam asmeniui rūpintis savo sveikata, prisiimti pareigą pagal išgales prisidėti prie jos priežiūros finansavimo, atsakingai ir racionaliai naudotis sveikatos priežiūros paslaugomis; todėl pagal Konstituciją įstatymų leidėjas turi įgaliojimus nustatyti, kad už tam tikras sveikatos priežiūros paslaugas turi būti atsiskaitoma iš privačių finansavimo šaltinių, kaip antai iš savanoriškojo sveikatos draudimo fondų lėšų, tiesioginiais pačių asmenų mokėjimais ir kitais būdais <...>" 21 . Reikia pažymėti, kad, siekiant geresnės visuomenės sveikatos, didžiulę reikšmę turi solidarumo 22 ir sveikatos priežiūros teisumo 23 principai: visuomenės nariai yra raginami solidarizuotis, tai praktikoje pasireiškia kaip lygios galimybės siekti sveikatos; socialinių skirtumų nebuvimas 24 ; kiekvieno žmogaus teisė siekti sveikatos; skaidrūs sveikatą lemiančių veiksnių paskirstymai; dėmesys labiausiai pažeidžiamų žmonių sveikatai 25 . Sveikatos priežiūros teisumo principo samprata mokslo darbuose glaudžiai siejama su vienoda sveikatos priežiūros paslaugų kokybe visiems pacientams, vienodu sveikatos priežiūros paslaugų prieinamumu vienodus poreikius turintiems pacientams ir vienoda sveikatos būkle visose visuomenės grupėse, neatsižvelgiant į socialinę ir ekonominę padėtį 26 .…”
Section: Pareiga Rūpintis Savo Sveikata Ir Visuomenės Akceptuoti Sveiunclassified